أساليب التوضيح والتصريح فى الترجمة من العربية الى الانجليزية - عثمان، وليد (جامعة البترا الخاصة, 2006)
يهدف هذا البحث إلى استقصاء أساليب التوضيح والتصريح التي انتهجها مترجمو رواية "أفراح القبة" ورواية "قصر الشوق" للأديب المصري "نجيب محفوظ" والبحث من حيث موضوعه لا يصنف ضمن حقل "نقد الترجمات" وإنما هو محاولة لجمع وتلخيص أساليب التوضيح والتصريح التي كشف عنها منظرون وباحثون في مجال علم الترجمة الوصفي، وبالتحديد في ميادين دراسات النصوص المترجمة وغير المترجمة. وقد كشفت الدراسة لنصوص هذا البحث عن بعض الأساليب التي انتهجها المترجمون في سبيل جعل النص أكثر وضوحا للقارئ. This paper is an investigation of the explicitation techniques employed by the translators of Afrah al-Qubbah, and Qasr el-Shawq, two novels by the Nobel Laureate, Naguib Mahfouz (1981; 1984)(1). The ultimate objective of the paper, however, does not lie within the domain of translation criticism; rather, it is an attempt to put in one study the several explicitation techniques suggested by a number of scholars researching into the remit of Corpus-Based Translation Studies and Translation Universals (TU) - both lying within the wider field of Descriptive Translation Studies (DTS). The manual investigation of the corpus of this study resulted in citing examples of several explicitation techniques; namely, explanation of cultural material, additions and insertions, substitutions, spelling out of implicatures, and resolving ambiguities.
ملخص لبحث منشور باللغة الانجليزية
Keywords: الروايات العربية -- مستخلصات الابحاث -- الترجمة -- اللغة العربية -- اللغة الانجليزية -- الادب العربى -- محفوظ ، نجيب ، ت 2006 -- رواية أفراح القبة -- رواية قصر الشوق -- المترجمون